Cutaneous Mycobacterium intracellulare infection presenting as multiple asymptomatic papulonodules in an immunocompetent adult: A case report and review of the literature - Yen-Yun Tsai; Po-Ren Hsueh; Cheng-Hsiang Hsiao; Tsen-Fang Tsai (Wolters Kluwer Medknow Publications, 2013)
Disseminated cutaneous nontuberculous mycobacteria infection is rare in immunocompetent hosts. We report a case of Mycobacterium intracellulare infection in an immunocompetent patient presenting with simultaneously developing multiple asymptomatic cutaneous papulonodules. The possibility of lung lesions as the primary focus is suspected. We review the literature for other cases of multiple cutaneous M avium complex infections in immunocompetent hosts. There are differences in the virulence of M avium and M intracellulare, and hence in the underlying immune status of the hosts.